Barriers and Drivers of the Implementation and Management of Green Agri-Food Supply Chains in Azerbaijan - Mehdiyeva, Irada; Kerimli, Vugar; Gafarov, Nizami; Sultanova, Naila; Heydarova, Kufiya; Taghiyev, Ayaz (International Journal of Supply Chain Management, 2020)
Abstract— The object of the study is the barriers and drivers of the implementation and management of green agricultural supply chains in Azerbaijan. The main characteristics of the country's agricultural logistics have been considered; it was found that the development of agriculture is one of the most important non-oil sectors of the country. Recently, the introduction of advanced technologies in agriculture has been observed; this is evidenced by an increase in labor productivity and the expansion of organic farmland. The hypothesis of the study is that productivity in agriculture (including, organic farming) directly correlates with the volume of investments in the development of transport and storage. Statistical confirmation of the research hypothesis allowed us to highlight the development of the logistics infrastructure as the main driver of the implementation and management of green agricultural supply chains. The negative factors hampering the industry development are the lack of modern storage facilities, transport infrastructure, state support for agricultural producers, the lack of information technologies for supply chain management and cooperation between agricultural producers. Within the framework of the study, the feasibility of an agricultural cluster has been proposed and substantiated. A model to increase the competitiveness of agricultural producers has been developed.